The Perceived Social Support, Dysfunctional Attitude, Resilience and Quality of Life in Hemiplegic Paralyzed Patients - Shoukat, Nadeem; Khawar, Rabia (Pakistan Armed Forces Medical Journal, 2023)
Objectives: To assess how perceived social support and dysfunctional attitudes influence the quality of life of hemiplegic paralysed patients and the role of resilience in changing the dysfunctional attitudes of these patients.Study Design: Cross-sectional study.Place and Duration of Study: Allied Hospital Neurology/Medicine Department, Ali Poly Clinic, and Bukhari Homeopathic Clinic Faisalabad Pakistan, from Mar to Jul 2022.Methodology: Two hundred and ten hemiplegic paralysed patients were included in the study. Multidimensional Scale for Perceived Social Support, Dysfunctional Attitude Scale, Brief Resilience Scale, and World Health Organization Quality of Life –Bref were used for data collection.Results: Findings demonstrated significant mean difference across age groups on quality of life [F (2, 207) = 17.34, p